ANALISIS HUBUNGAN ANTARA KEBIJAKAN MAKROPRUDENSIAL DAN KEBIJAKAN MONETER TERHADAP PERTUMBUHAN KREDIT DI INDONESIA - Fajar Indanil Bakti; Dewi Zaini Putri (Universitas Negeri Padang, 2019)
This study examines the causal relationship beetwen macroprudential policy, and monetary policy on credit growth within a vector error corellations model (VECM) forIndonesia countries over the period November 2013 until Oktober 2018. The results of this study indicate that the macropruential policy and the credit growth does not have causality relationship, and the monetary policy and the credit growth has a causality relationship.